Chaucer's queer poetics : rereading the dream trio - Schibanoff, Susan (University of Toronto Press, 2006)
This study challenges the long held view the Chaucer fled the prison of effete French court verse to become the 'natural' English father poet and charts a new model of Chaucerian poetic development that discovers the emergence of a queer aesthetic in his work.